(untitled) (Linguist, 2026)
This study examines the impact of Transformational Leadership (TL) behaviours on the acquisition of essential soft skills among students at Mohammed I University. It explores the interplay between TL, soft skills, and the organisational culture of higher education, focusing specifically on university extracurricular activities within student clubs. The findings reveal that TL behaviours, including Idealized Influence, Inspirational Motivation, Individualized Consideration, and constructive feedback, promote personal mastery, resilience, adaptability, and leadership capacity among students. Participants highlighted the role of trust, transparency, and motivational guidance as key mechanisms through which leaders facilitate both self-directed growth and interpersonal development. These results underscore the practical importance of integrating TL principles into extracurricular and instructional activities to enhance skill acquisition, team cohesion, and social participation. By demonstrating how student clubs can serve as transformative contexts for leadership and soft skill development, this study addresses a notable gap in the literature.